Gibbs Free Energy Calculation of Mutation in PncA and RpsA Associated With Pyrazinamide Resistance - Khan, Muhammad Tahir; Ali, Sajid; Zeb, Muhammad Tariq; Kaushik, Aman Chandra; Malik, Shaukat Iqbal; Wei, Dong-Qing (Frontiers in Molecular Biosciences, 2020)
A central approach for better understanding the forces involved in maintaining the protein structures, is to investigate the thermodynamic properties of mutations on protein folding. The folding process is most often affected in the native and mutated states. Molecular dynamic (MD) simulations have been widely applied in exploring the mechanisms of conformational changes in protein, especially in drug resistance mechanisms behind mutations. When comparing wild type (WT) and mutants (MTs), the structural changes along with stability, flexibility, Solvation free energy (SFE), and Gibbs free energy (GFE) are calculated after the MD simulation to measure the effect of mutations. PZA-resistance that mainly emerges due to mutations in pncA and rpsA genes encoding pyrazinamidase (PZase) and ribosomal protein S1 (RpsA) respectively, is a global problem, effecting the TB control program 2030. The question that how the GFE may be a measure of PZase and RpsA stabilities, has been addressed in the current review. The GFE and SFE of MTs have been compared with WT which were already been found PZA-resistance. WT structures attained a more stable state in comparison with MT’s PZase and RpsA. The physiological effect of a mutation in drug target might be the difference in energies. This difference between WT and MTs depicted through GFE plots, might be useful in calculating of stability and PZA-resistance behind mutation for better management and alternative drug discovery to control the global TB resistance problem.